La conception du temps chez les Wayana - Lapointe, Jean (Anthropologica, 2022)
This article explores the different dimensions of the conception of time among a group of horticulturalists, and attempts to account for their experience of time. Among the Wayana, a Carib tribe of the Amazon, we find very little of the cumulative aspect of temporal experiences which are dominant in historical societies.